An OWL ontology for ISO-based discourse marker annotation - Chiarcos, Christian; Silvano, Purificação; Damova, Mariana; Valūnaitė Oleškevičienė, Giedrė; Liebeskind, Chaya; Trajanov, Dimitar; Truica, Ciprian-Octavian; Apostol, Elena-Simona; Bączkowska, Anna (My University, 2022)
Purpose: Discourse markers are linguistic cues that indicate how an utterance relates to the discourse context and what role it plays in conversation. The authors are preparing an annotated corpus in nine languages, and specifically aim to explore the role of Linguistic Linked Open Data (/LLOD) technologies in the process, i.e., the application of web standards such as RDF and the Web Ontology Language (OWL) for publishing and integrating data. We demonstrate the advantages of this approach.